Effectiveness of patient education training on health professional student performance: A systematic review. Issue 10 (October 2021) - Forbes, Roma; Clasper, Bennita; Ilango, Anusha; Kan, Haeley; Peng, Julia; Mandrusiak, Allison
Highlights: Training enhances health professional students' performance of patient education. Simulation-based training of patient education appears to be most effective. Future research is needed to evaluate specific approaches to training. Abstract: Background: Despite the fundamental role of patient education, concerns have been raised by health professionals, students, and professional bodies regarding student preparation for this area of practice. Objective: To evaluate the effectiveness of patient education training on health professional student performance. Method: A systematic search was performed across PubMed, Cinahl, Embase, and Cochrane Library. Reference and forward citation searches of included articles were conducted. Inclusion criteria were published journal articles from 2010 to 2020 regarding patient education training for health professional students with measures relating to patient education performance. Quality appraisal of individual studies was conducted using Cochrane risk-of-bias v2 or ROBINS-I; overall appraisal was also determined. Sixteen articles met eligibility criteria. Independent data extraction was undertaken. Results: Fourteen studies reported improvements in student performance following patient education training; two studies reported no significant improvements. Of different modalities examined, simulation-based learning appeared to be most effective. Conclusion: Patient education training enhances health professional students' performance of patient education. Future research is needed to evaluate effectiveness of pedagogically informed interventions across health professions using objective approaches to assess student performance in clinically relevant settings. Practical Value: This review supports the use of specific training approaches to improve student performance of patient education.